PERSYARATAN SUKSESOR GEREJA SUARA KEBENARAN INJIL - Grant Nixon (Sekolah Tinggi Teologi Ekumene Jakarta., 2020)
Succession in an organization cannot be separated from certain requirements of a successor that is expected to be in line with the organization's vision, mission, and values. Therefore, Gereja Suara Kebenaran Injil (GSKI) as an organization must have a description of the successor's accommodative requirements in realizing the interests of the organization in the future. This paper aims to describe the successor requirements that are accommodating to the needs of the GSKI organization in the future based on field findings and a biblical study of Joshua as a successful successor model. The requirements found were proposed as a constructive recommendation for the standard and accommodating successor requirements within the GSKI body. This research uses a qualitative method with a grounded theory approach. Data collection techniques were carried out through interviews with stakeholders and literature studies. Data were analyzed by synthesizing the findings in the literature study and interviews. The synthesis between interview findings and literature study produced a conceptual framework regarding accommodative successor requirements. The analysis shows that the requirements of accommodative GSKI successors are those who have a healthy and consistent spirituality, educated teachers, pastors who are skilled in pastoral care, accomplished organizers and person who has the vision to improve organizational quality collectively. This research concludes that the requirements of the GSKI successors in the future are deeply intersected with the quality of the present GSKI leader. Achieving this is greatly influenced by an effective mentoring and empowerment process.